Evaluación de factores económicos y financieros en la empresa de transporte maurat transmau s.a en el año 2021 - Saldivia Guerrero, María Isabel (2022)
Currently, companies are in a business world which are inserted in a dynamic and changing environment that affects business performance. The problem of measuring economic factors brings as a consequence an enormous difficulty in detecting inefficiencies and correcting them, or in another case in trying to make processes more efficient. In the search for support for social and economic development, the transport company MAURAT TRANSMAU S.A. you must use in a good way all the capital you have in the development of your main business. The performance of the company in a certain economic category is reflected in its ability to use human and material resources to achieve its objectives. The objectives of this research are to evaluate the economic and financial factors of the transport company MAURAT TRANSMAU S.A., to detect the weak points that may threaten the continuity of the company. The methodological approach used for the collection of information necessary for the structuring of the present case study case was qualitative, for which the identification of the information required according to the agreement was allowed.